1995
DOI: 10.1006/dbio.1995.1146
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of NGF within the Heart of Transgenic Mice Causes Hyperinnervation, Cardiac Enlargement, and Hyperplasia of Ectopic Cells

Abstract: Nerve growth factor (NGF) supports the survival of developing sympathetic and a subpopulation of sensory neurons. In the adult it participates in maintenance of the neurotransmitter phenotype of responsive neurons. The amount of NGF synthesized by a given target tissue determines its final innervation density; those developing neurons that fail to receive sufficient NGF undergo apoptosis. In order to examine the ramifications of this principle in the context of a specific target organ, a transgenic mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(109 citation statements)
references
References 0 publications
4
105
0
Order By: Relevance
“…For example, ARTN expression in VSMCs shifts from central to peripheral blood vessels in parallel with sympathetic axon extension along these vessels (Honma et al, 2002). In the developing heart, NGF is important for sympathetic innervation of the myocardium (Hassankhani et al, 1995;Ieda et al, 2004). In Ngf −/− ; Bax −/− embryos, there appears to be normal sympathetic axon extension along the extracardiac vasculature but a drastic decrease in sympathetic innervation of the heart .…”
Section: Discussionmentioning
confidence: 99%
“…For example, ARTN expression in VSMCs shifts from central to peripheral blood vessels in parallel with sympathetic axon extension along these vessels (Honma et al, 2002). In the developing heart, NGF is important for sympathetic innervation of the myocardium (Hassankhani et al, 1995;Ieda et al, 2004). In Ngf −/− ; Bax −/− embryos, there appears to be normal sympathetic axon extension along the extracardiac vasculature but a drastic decrease in sympathetic innervation of the heart .…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic mice overexpressing NGF in the heart show elevated cardiac catecholamine levels and sympathetic hyperinnervation. 23, 24 Cao et al 25 reported that a prolonged (5 weeks) infusion of NGF into the left stellate ganglion of dogs after myocardial infarction induces hyperinnervation, which results in ventricular tachyarrythmias and sudden cardiac death. However, in vivo, nerve sprouting was not observed as early as 1 week after the beginning of NGF application.…”
Section: Discussionmentioning
confidence: 99%
“…2 Therefore, a doubled NE reuptake in the latter study is rather caused by the previously reported cardiac hyperinnervation in these mice. 24 How does NGF improve NET function? We did not observe a change of NET mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve growth factor (NGF) is the main neurotrophic factor that crucially controls the sympathetic tone of the mammalian heart (Levi-Montalcini 1976;Snider 1994;Hassankhani et al 1995). In parallel, NGF has been identified as a pro-survival factor for cardiomyocytes by developing anti-apoptotic effects via tyrosine kinase A (TrkA) receptor downstream signaling (Caporali et al 2008).…”
Section: Introductionmentioning
confidence: 99%